Strain for toughened epoxy resin composites for GIL tri‐post insulators under tension and electric fields - Liucheng Hao; Weibin Ren; Rui Chen; Yaxiang Wang; Minzheng Yang; Mufeng Zhang; Duanpeng Yuan; Yang Shen (IET Nanodielectrics, 2024)
Abstract Toughening plays a key role in epoxy resins (EPs) and their composites for high voltage gas‐insulated switchgear (GIL) tri‐post insulators and receives a lot of attention. However, there are still limited research studies on strain and its distribution for the toughened EPs and composites under tension and especially under high electric fields. Herein, the intrinsically toughening mechanism of EPs (toughening ability: EP‐B > EP‐A) and their composites with Al2O3 (toughening ability: EP‐Bcom > EP‐Acom) was explored in terms of chemical characterisation by IR and molecular motion via differential scanning calorimetry and dielectric spectra. A low rigid segment content in EPs contributes to the excellent toughness. Two‐dimensional digital image correlation (2D‐DIC) and three‐dimensional DIC (3D‐DIC) were utilised to probe strain and its distribution in EPs and their composites under tension and electric fields, respectively. EP‐B with more toughness endows it with a larger strain εF under tensile fields and a greater strain amplitude |εE| under electric fields than EP‐A, such as 9278 με at 1 kN, 16.9% greater than EP‐A and 9767 με at 10 kV/mm, 19.3% higher than EP‐A. In addition, all samples show minus strain under electric fields due to compression. With the introduction of Al2O3, EP‐Bcom exhibits a εF of 2870 με at 1 kN, 69.1% lower than that of EP‐B and 49.4% greater than that of EP‐Acom, and it provides |εE| of 5351 με at 10 kV/mm, 45.2% lower than that of EP‐B and 13.2% greater than that of EP‐Acom. Further, samples with more toughness deliver more uniform strain distribution whether under tension or electric fields.